Application of zinc-aluminium layered double hydroxides for adsorptive removal of phosphate and sulfate: Equilibrium, kinetic and thermodynamic. (October 2018) - Iftekhar, Sidra; Küçük, Mehmet Emin; Srivastava, Varsha; Repo, Eveliina; Sillanpää, Mika
Abstract: In this study, a series of layered double hydroxide (ZxAy LDH) material was synthesized with different molar ratios and calcination temperatures to remove phosphate and sulfate ions from synthetic solution. ZxAy LDH was characterized by XRD, FTIR, BET and SEM analysis. The highest removal was obtained by Z3A200 LDH that is LDH with a Zn-Al molar ratio of 3 and calcined at 200 °C. The leaching of Zn and Al was more under highly acidic pH compared to pH 5 and 8. Adsorption isotherms data had a good fit with Langmuir model and maximum adsorption under optimum conditions led to 2.6–2.72 and 1.02–1.31 mmol/g for phosphate and sulfate, respectively. Kinetic studies have been performed by applying reaction based models and diffusion-based models, which indicated the chemisorption interaction for Z3A200 by a controlling step of the macro-pore and micro-pore diffusion for phosphate and sulfate adsorption process onto Z3A200, respectively. Thermodynamic studies showed that adsorption process onto Z3A200 was endothermic and spontaneous. Thus, phosphate and sulfate adsorption by using optimized Zn-Al LDH appears to be a promising adsorbent for their removal. Highlights: ZxAy LDH has been employed for phosphate and sulfate removal. Z3A200 LDH showed highest removal for phosphate and sulfate. Zn and Al leaching was more at pH 2 compared to pH 5 and 8. Experimental data fitted well to Langmuir and pseudo second order model. Z3A200 LDH is promising adsorbent for phosphate and sulfate removal.